Design of natural-language interfaces for reference systems - Yu. S. Hetsevich; V. A. Zhitko; S. A. Hetsevich; L. I. Kaigorodova; K. A. Nikalaenka (Informatika)
The description of the technology of modern natural language interfaces for intelligent systems and language interfaces for question-answering intelligent systems is presented, as well as methods and principles for their design. Analysis of the intelligent systems with natural language interfaces used in different areas are given. These areas are medicine, smart home technology, education, industry, fast adaptation to new technologies. The list of the most popular services with the natural language interfaces is presented. Each service can be used as a ready-to-use personal assistant or as a core for the development of a new customized natural language interface. The research of the natural language interfaces was conducted from the point of view of the natural language usage for the interaction between a user and the machine. The main problems here are the bias in natural language and the difficulties in the design of natural language interfaces that meet user expectations. The main principles of modeling of natural language interfaces are considered. As an intelligent system the interface consists of the database, knowledge machine and user interface. Speech recognition and speech synthesis components make natural language interfaces more convenient from the point of view of usability.